HUBUNGAN FAKTOR RISIKO DAN KEPATUHAN TERHADAP TERAPI DENGAN KEJADIAN STROKE ISKEMIK ULANG - Bambang Bhayu Herlambang,* Ahmad Rizal Ganiem,* Aih Cahyani* (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION HISTORY OF PREVIOUS STROKE IS ONE OF THE PROMINENT OF MANY RECURRENT STROKE RISK FACTORS THE INCIDENCE OF RECURRENT STROKE IS 2030 OF ALL STROKE POPULATION WHILE THE RECURRENT ISCHEMIC STROKE IN 5 YEARS MAY REACH UP TO 40 RECURRENT STROKE IS ASSOCIATED WITH LONGER DURATION OF HOSPITALIZATION INCREASED NEUROLOGIC DISABILITY AND DEATH